2018
DOI: 10.1155/2018/4020625
|View full text |Cite
|
Sign up to set email alerts
|

Radial Head Resection versus Arthroplasty in Unrepairable Comminuted Fractures Mason Type III and Type IV: A Systematic Review

Abstract: Unrepairable comminuted fractures of the radial head Mason type III or type IV have poor outcomes when treated by open reduction and internal fixation. Radial head resection has been proposed as good option for surgical treatment, while in the last decades, the development of technology and design in radial head prosthesis has increased efficacy in prosthetic replacement. The present review was conducted to determine the best surgical treatment for comminuted radial head when ORIF is not possible. Better outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…plates and screws, and cause a higher rate of failure of fixation, nonunion and osteonecrosis (13). This type of fracture is defined as "unsalvageable" or "unrepairable" radial head fractures (6,14) and are usually treated by radial head resection or arthroplasty.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…plates and screws, and cause a higher rate of failure of fixation, nonunion and osteonecrosis (13). This type of fracture is defined as "unsalvageable" or "unrepairable" radial head fractures (6,14) and are usually treated by radial head resection or arthroplasty.…”
Section: Resultsmentioning
confidence: 99%
“…So radial head arthroplasty has become the most popular treatment for such fractures. A wide variety of prostheses is available that is effective in preventing proximal migration of the radius which can increase dynamic stability of the elbow joint and DRUJ (5,6). Although radial head arthroplasty results in favorable outcomes, a number of mid to long-term retrospective studies have demonstrated that a considerable proportion of patients who undergo arthroplasty ultimately experience complications such as capitellum erosion, elbow joint arthrosis and loosening of the prosthesis (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Radial head arthroplasty (RHA) becoming a more popular option in recent years for the treatment of radial head fracture Mason type III and IV. Many studies state that RHA showed a superior result compared to radial head resection and open reduction and internal fixation, but some were against it, stating that the latter option is better in term of functional outcomes, number of revision surgery and post-operative early and late complications [ 1 , 3 , 4 , 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Catellani et al said that few papers recommend resection as a better option for isolated radial head fractures unassociated with ligaments injuries because of a lack of statistical clinical differences between RHA and radial head resection. No substantial differences in patient outcomes at medium and long-term follow-up [ 3 ]. A similar study from Akman et al show that resection arthroplasty is an effective method for the treatment of isolated comminuted radial head fractures because of the less demanding technique [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation